Colombia : Selected Issues Paper. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Selected Issues paper analyzes spillover risks for Colombia. It highlights that external shocks could spill over to the Colombian economy through the country's important and growing trade and financial linkages with the rest of the world. Colombia would be most exposed to a decline in oil prices, which could have a sizable adverse impact on the balance of payments, the fiscal accounts and growth. Growth shocks in key trading partners could also have a negative impact, particularly in the United States, which is Colombia's main trading partner. Colombia's fiscal rule and adjustment in the context of resource wealth is also analyzed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet